Evaluation of light dependence of monoterpene emission and its effect on surface ozone concentration. (March 2015) - Nishimura, Hiroshi; Shimadera, Hikari; Kondo, Akira; Bao, Hai; Shrestha, Kundan Lal; Inoue, Yoshio
Abstract: This study evaluated the effect of light intensity on monoterpene emission from the three dominant coniferous tree species in Japan ( Cryptomeria japonica, Chamaecyparis obtusa and Pinus densiflora ). Monoterpene emission experiments were conducted by using a growth chamber where temperature and light intensity can be controlled. In the experiments, air temperature was set at 30 °C and light intensity was set at 0, 500, 700, 850, 1200, and 1400 μmol m −2  s −1 . Because monoterpene emissions from the three tree species similarly increased with increasing light intensity, a new empirical equation considering light dependence was proposed to estimate monoterpene emission. In addition, monoterpene emission in the Kinki region of Japan was estimated with and without light dependence using meteorological field produced by the Weather Research and Forecasting model (WRF) in summer 2010. The monoterpene emissions estimated with light dependence were larger than those without light dependence in the daytime under clear sky conditions and consistently smaller in the nighttime. In order to evaluate the effect of light dependence of monoterpene emission on ozone concentration in the Kinki region, two cases of air quality simulations by the Community Multiscale Air Quality model (CMAQ) were conducted using the monoterpene emission data estimated with and without light dependence. Comparisons of the two cases showed that the monoterpene emission changes due to light dependence slightly but systematically affected ozone concentrations. Monoterpene generally played a role of reducing ozone concentration in the CMAQ simulations. Consequently, because of the light dependence, the mean daily maximum ozone concentrations decreased by 0.3 ppb on average with a maximum of 2.2 ppb, and the mean daily minimum values increased by 0.4 ppb on average with a maximum of 1.8 ppb in the Kinki region in summer 2010. Highlights: Monoterpene emission from Japanese conifers was evaluated by growth camber method. Dependence of monoterpene emission rates on light intensity was clearly observed. Effect of light-dependent monoterpene emission on O3 was evaluated by WRF/CMAQ. Monoterpene generally played a role of reducing O3 concentration. Daytime monoterpene emission increase slightly reduced daily maximum O3 .